Unusual Vestibulo-Ocular Reflex Responses in Patients With Peripheral Vestibular Disorders Detected by the Caloric Step Stimulus Test - Honjo, Motomu; Honda, Keiji; Tsutsumi, Takeshi (Frontiers in Neurology, 2020)
The caloric step stimulus test consists of the changes in head position from the sitting to supine positions and continuous caloric irrigation. This test can provide a single labyrinth with a stimulus similar to constant head acceleration in rotational testing and, therefore, can evaluate vestibulo-ocular reflex (VOR) dynamics more precisely than can conventional methods. To assess the clinical utility of the test in the assessment of the VOR dynamics of diseases, we performed the test in patients with peripheral vestibular disorders, including sudden idiopathic hearing loss, vestibular neuritis, Meniere disease, vestibular Meniere disease, or chronic unilateral idiopathic vestibulopathy and normal controls. Slow-phase eye velocity (SPV) was measured with videonystagmography. We fitted the time course of SPV across 2 min to a mathematical model containing two exponential components and time constants: the caloric step VOR time constant (T1) and caloric step VOR adaptation time constant (T2). All responses of normal controls (n = 15 ears) were fit to the model. Several responses of the 101 ears of the patients differed from the time courses predicted by the model. We classified the data of 116 ears into four patterns based on SPV, T1, and T2. The thresholds for the classification were determined according to the lower limits of the capability of curve fitting for SPV and the upper limits of normal controls for T1 and T2. Seventy-eight ears followed pattern A (normal T1 and T2): the SPV trajectory formed a rapid rise with subsequent decay. Nineteen followed pattern B (normal T1 and prolonged T2): the SPV trajectory formed a rapid rise without decay. Six followed pattern C (prolonged T1 and T2): the SPV trajectory formed a slow rise. Thirteen ears followed pattern D: a low VOR response. There were no significant differences in time constants between the affected and healthy ears in patients with each disease. However, prolonged T1 and T2 were significantly more frequent in the affected ears than the healthy ears. In conclusion, the caloric step stimulus test can be potentially useful in detecting unusual VOR responses and thus reflect some pathological changes in the vestibular system.